PEMATANGAN GONAD IKAN SEPAT SIAM Trichogaster pectoralisRegan JANTAN MENGGUNAKAN JENIS MAKANAN YANG BERBEDA - Sukendi Sukendi; Ridwan Manda Putra; Nur Asiah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
The aimed of this research was to investigate the best fish meal for triger thematuration of male Trichogaster pectoralis Regan. Male fishes were reared infloating cages (1m x 1m x 1m) that were placed in fish ponds, 8 females and 8males/ cage, 3 repititions. The fish were reared for 56 days and were feed ondifferent types of meal, P1 ( Tubifex sp), P2 (shrimp) and P3 (Vit E + shrinp).Parameters measured were maturity level, semen volume, spermatozoaconcentration, spermatozoa viability and spermatozoa motility. The best resultwas achieved at P3 (shrinp + vit E) as 16 fishes achieved 4th maturity level, semenvolume was 0,214 ml, spermatozoa concentration was 19,543 x 10 9 sel/ml,spermatozoa viability was 83,455 % and spermatozoa motility was 79,750 %.Keywords :Trichogaster pectoralis,semen volume,spermatozoa cooncentration, spermatozoa viability and spermatozoa motility